2011
DOI: 10.3389/fpls.2011.00042
|View full text |Cite
|
Sign up to set email alerts
|

Silencing ?1,2-xylosyltransferase in Transgenic Tomato Fruits Reveals xylose as Constitutive Component of Ige-Binding Epitopes

Abstract: Complex plant N-glycans containing β1,2-xylose and core α1,3-fucose are regarded as the major class of the so-called “carbohydrate cross-reactive determinants” reactive with IgE antibodies in sera of many allergic patients, but their clinical relevance is still under debate. Plant glycosyltransferases, β1,2-xylosyltransferase (XylT), and core α1,3-fucosyltransferase (FucT) are responsible for the transfer of β1,2-linked xylose and core α1,3-linked fucose residues to N-glycans of glycoproteins, respectively. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 51 publications
0
10
0
3
Order By: Relevance
“…However, the clinical relevance of these reactive IgE remains unclear. Strasser et al used RNAi to successfully silence XylT, the gene coding for β1,2-xylotransferase, in tomato plants and demonstrated a patient-specific reduction in IgE reactivity in their studies ( Paulus et al 2011 ). Arabidopsis thaliana knockouts of the XylT (encoding β1,2-xylotransferase) and FucT (encoding α1,3 fucosyl transferase) genes have also been generated that are viable with no obvious phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…However, the clinical relevance of these reactive IgE remains unclear. Strasser et al used RNAi to successfully silence XylT, the gene coding for β1,2-xylotransferase, in tomato plants and demonstrated a patient-specific reduction in IgE reactivity in their studies ( Paulus et al 2011 ). Arabidopsis thaliana knockouts of the XylT (encoding β1,2-xylotransferase) and FucT (encoding α1,3 fucosyl transferase) genes have also been generated that are viable with no obvious phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…Three putative genes, of which the translated amino acid sequences showed 12–16% of identity with XTA , were identified as Cre10.g458950, Cre13.g588750 and Cre08.g361250. XTA, XTB and the three additional putative C. reinhardtii xylosyltransferases were compared with core β(1,2)‐xylosyltransferases previously functionally characterized in A. thaliana (Strasser et al , ), Solanum lycopersicum (Paulus et al , ), Oryza sativa (Shin et al , ), Lemna minor (Cox et al , ), Medicago sativa (Sourrouille et al , ) and Physcomitrella patens (Koprivova et al , ; Figure ). The phylogenic tree showed that C. reinhardtii and plant xylosyltransferases are distributed in two distinct clades (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…Mehrere Tomatenallergene konnten zwischenzeitlich mittels RNAi-Silencing supprimiert werden [51,54,55]. Die reduzierte oder nicht vorhandene IgE-Reaktivität der allergenreduzierten Tomaten konnte auch in den nachfolgenden Tochtergenerationen bestätigt werden, was darauf hinweist, dass das RNAi-Silencing über mehrere Generationen stabil bleibt.…”
Section: Apfel (Malus Domestica)unclassified
“…Bezüglich der Reduktion der Allergenität von Sola l 2 (Invertase) wurde ein anderer Ansatz gewählt [55]: Es konnte gezeigt werden, dass das IgEbindende Epitop im Tomatenallergen Sola l 2 eine β-1,2-gebundene Xylose enthält. In P anzen wird der Transfer der Xylose von Uridindiphosphat(UDP)-Xylose an die Kern-Mannose ("core mannose") von N-Glykanen durch das Enzym β-1,2-Xylosyltransferase vermittelt.…”
Section: Apfel (Malus Domestica)unclassified
See 1 more Smart Citation